PENGEMBANGAN PROSES BISNIS DI PUSAT KEUNGGULAN UNTUK MENINGKATKAN OPTIMASI OPERASIONAL - Frisca Yuliana Hutagalung; Tia Rivani; Sarima Siregar; Nadia Fathurrahmi Lawita; Dewi Junita; Susi Lestari; Izzatul Jannah (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This research aims to develop business processes at the Center of Accounting and Fintech (CoE Afintec) Polibatam. The analysis of this business process development is an effort to improve operational efficiency and support the achievement of the strategic goals of CoE Afintec. The research method used is a qualitative method with an applied research type, which is focused on solving real problems faced by CoE Afintec. Data were collected through in-depth interviews with related parties and then analyzed using a BPMN (Business Process Model and Notation)-based Business Process Diagram (BPD) to map core processes and see positive and negative values. The research results showed that several processes were not running effectively and optimally. Based on these results, a new business process was redesigned to be more structured, responsive, and in line with the needs and objectives of CoE Afintec development. With the development of this business process, it is hoped that CoE Afintec Polibatam can strengthen its role sustainably as a center of excellence that supports the Tridharma of Higher Education and becomes a profit center for the Polibatam Business Management Department.